TEMPERATURE MEASUREMENTS IN THE CRATER OF MOUNT EREBUS, ROSS ISLAND, ANTARCTICA (2) - シミズ, ヒロシ; カミヌマ, カツタダ /; SHIMIZU, Hiroshi; KAMINUMA, Katsutada; DIBBLE, Raymond R. (National Institute of Polar Research, 1991)
P(論文) Surface temperature distribution in the crater of Mount Erebus, Ross Island, Antarctica was surveyed during the 1989-1990 field season using an infrared radiation thermometer. A convecting lava lake with the diameter of about 20 to 30m was observed in the inner crater of the main crater. The maximum surface temperature of the inner crater was 118℃. departmental bulletin paper